A history of Canadian recruitment of highly skilled immigrants: circa 1980 - 2001 - Don J. DeVoretz (Institute for the Study of Labor (IZA), 2006)
This paper identifies the types of immigrants that Canada has recruited to foster modern Canadian economic development and assesses how effective Canada has been in recruiting and retaining these required immigrants in the 21st century. Evidence from both balance of trade and balance of payments exercises indicates that it is difficult to determine if there actually exist positive net inflows of managers and professionals during the 1982-2001 period. The entry of these highly skilled immigrants resulted from a series of distinct labour market policies adopted by Citizenship and Immigration Canada and its predecessor agencies. The paper presents evidence to support that between 1976-1990 a tap on-tap off policy admitted skilled immigrants to Canada only if a labour vacancy was anticipated. However, after 1990 tests reveal that the previous year's economic immigrant admissions determined the contemporary immigrant flows with a 10 month lag. Offsetting this robust admission of economic immigrants in the 1990's was the substantial outflows of previous Canadian immigrants as part of the rising phenomenon of brain circulation. Of particular note is the large number of highly skilled Chinese who have returned to Hong-Kong after 1997. Given this brain circulation and the chronic underutilization of its highly trained immigrants I conclude that Canada's traditional use of immigrants as an engine of growth is very limited in the 21st century and suggest recruitment of foreign graduate students to revitalize the role of immigrants in Canadian development.
Keywords: J61; J68; 330; immigration policy